Development of a gender-specific European job exposure matrix (EuroJEM) for physical workload and its validation against musculoskeletal pain - Solovieva, Svetlana; Descatha, Alexis; Mehlum, Ingrid Sivesind; Viikari-Juntura, Eira; Undem, Karina; Berglund, Karin; Gilbert, Fabien; Wuytack, Francesca; d’Errico, Angelo; Badarin, Kathryn; Evanoff, Bradley; Kjellberg, Katarina (Scandinavian Journal of Work, Environment & Health, 2025)
' ' OBJECTIVES ': 'The aim was to develop a gender-specific European job exposure matrix (EuroJEM) for occupational physical workload and study its predictive validity for musculoskeletal pain in four European cohorts. ' ' METHODS ': 'National, gender-specific JEM from Finland, France, Norway and Sweden, based on self-reported exposure information, were evaluated for similarities in exposures, exposure definitions, and occupational coding. The EuroJEM harmonized five exposures: heavy lifting, faster breathing due to heavy workload, kneeling/squatting, forward bent posture, and working with hands above shoulder level. Our expert panel addressed disagreements and missing information to reach consensus on exposure levels across occupations. To assess predictive validity of the EuroJEM, we examined associations between the harmonized exposure measures and self-reported musculoskeletal pain across the four cohorts. ' ' RESULTS ': 'The EuroJEM provides semi-quantitative exposure estimates for 374 ISCO-88 (COM) occupational codes. Five categories of exposure were defined by the proportion of workers exposed within each occupation. Comparable and statistically significant associations were found between EuroJEM exposures and low back, shoulder, and knee pain across all cohorts and genders, except for knee pain among women in the Finnish cohort. For instance, in both genders heavy lifting, faster breathing due to heavy workload, and forward bent posture were statistically significantly associated with low-back pain in all four cohorts, with OR ranging from 1.25–2.18 (men) and 1.23–2.04 (women). ' ' CONCLUSIONS ': 'Despite differences in study populations and outcome definitions, good predictive validity was observed in each national cohort, suggesting that EuroJEM can be an effective tool for exposure assessment in large-scale European epidemiological studies.
Keywords: epidemiological study; EuroJEM; gender; gender-specific European job exposure matrix; harmonization; job exposure matrix; musculoskeletal pain; physical workload; predictive validity; validation